2020
DOI: 10.3390/cells9051201
|View full text |Cite
|
Sign up to set email alerts
|

Progerin Expression Induces Inflammation, Oxidative Stress and Senescence in Human Coronary Endothelial Cells

Abstract: Hutchinson–Gilford progeria syndrome (HGPS) is a rare premature aging disorder notably characterized by precocious and deadly atherosclerosis. Almost 90% of HGPS patients carry a LMNA p.G608G splice variant that leads to the expression of a permanently farnesylated abnormal form of prelamin-A, referred to as progerin. Endothelial dysfunction is a key determinant of atherosclerosis, notably during aging. Previous studies have shown that progerin accumulates in HGPS patients’ endothelial cells but also during va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 55 publications
3
39
0
Order By: Relevance
“…Consistent with previous studies (Bidault et al, 2020;Liu et al, 2019), we observed that IL6 secretion is increased in HGPS fibroblasts carrying the classical G608G LMNA mutation and also in fibroblasts from Mandibuloacral Dysplasia, another LMNAlinked progeroid syndrome (Cenni et al, 2018;Filesi et al, 2005) ( Figure 1a and Figure S1a). Further, the LMNA delta 50 mutation causing progerin expression, when transiently expressed in human HEK293 cells, induced hypersecretion of IL6 ( Figure 1b).…”
Section: Il6 Secretion Is Increased In Hgps Cellssupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies (Bidault et al, 2020;Liu et al, 2019), we observed that IL6 secretion is increased in HGPS fibroblasts carrying the classical G608G LMNA mutation and also in fibroblasts from Mandibuloacral Dysplasia, another LMNAlinked progeroid syndrome (Cenni et al, 2018;Filesi et al, 2005) ( Figure 1a and Figure S1a). Further, the LMNA delta 50 mutation causing progerin expression, when transiently expressed in human HEK293 cells, induced hypersecretion of IL6 ( Figure 1b).…”
Section: Il6 Secretion Is Increased In Hgps Cellssupporting
confidence: 92%
“…The moderate increase in life span obtained by tocilizumab administration suggests that pathogenetic pathways specifically relevant to animal survival were not rescued. For instance, despite amelioration of adipose tissue turnover and attenuation of IL6 signaling, metabolic effects related to dysregulation of other cytokines (Bidault et al, 2020; Griveau et al, 2020; Liu et al, 2019) might suddenly establish a fatal condition. Optimization of tocilizumab dosage and combination with drugs or molecular approaches already explored for HGPS treatment may pave the way to effective therapeutic strategies (Cenni et al, 2020; Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we found that ROS are induced by H/R injury in CECs and correlate with the survival of CECs by mediating mitochondrial bioenergetics. Similarly, it was previously reported that ischemia/reperfusion-mediated senescence and vascular dysfunction of endothelial cells were attenuated by oxidants [61]. Endothelial cell necroptosis is also induced by ROS-mediated opening of the mitochondrial permeability transition pore (mPTP) [62].…”
mentioning
confidence: 67%
“…In this context, cardiovascular diseases have been shown accelerated in HGPS patients and progerin, the abnormal form of prelamin-A, has also been shown to induces atherosclerosis and cardiac electrophysiological alterations (14). Furthermore, exogenously expressed progerin was showed increases inflammation (15). On the other hand, the AIM2 inflammasome has been shown to be activated after pharmacological alterations of the nuclear envelope integrity compatible with laminopathies (16).…”
Section: Discussionmentioning
confidence: 99%